2009
DOI: 10.2203/dose-response.09-039.mitchel
|View full text |Cite
|
Sign up to set email alerts
|

The Dose Window for Radiation-Induced Protective Adaptive Responses

Abstract: ᮀ Adaptive responses to low doses of low LET radiation occur in all organisms thus far examined, from single cell lower eukaryotes to mammals. These responses reduce the deleterious consequences of DNA damaging events, including radiation-induced or spontaneous cancer and non-cancer diseases in mice. The adaptive response in mammalian cells and mammals operates within a certain window that can be defined by upper and lower dose thresholds, typically between about 1 and 100 mGy for a single low dose rate exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 63 publications
1
51
0
Order By: Relevance
“…Since the direct biological consequences of low-dose irradiation are relatively subtle and difficult to measure, 7,8 we opted to study the radioadaptive response model to investigate the effects of low-dose radiation because animal studies have demonstrated such adaptive response. 6 We define doses at or below 0.1 Gy as low-dose radiation, 7 equivalent to the upper limit dose from a full-body spiral CT scan 8 and 2-4 Gy as high-dose radiation that causes substantial DNA damage to cells, 9,23 4 Gy is close to the LD50 for human whole-body exposure. 24 Using gH2AX as a surrogate marker of DNA damage, 23 we examined whether 0.1 Gy pretreatment of human fibroblasts could modulate cell sensitivity to a subsequent 4 Gy irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the direct biological consequences of low-dose irradiation are relatively subtle and difficult to measure, 7,8 we opted to study the radioadaptive response model to investigate the effects of low-dose radiation because animal studies have demonstrated such adaptive response. 6 We define doses at or below 0.1 Gy as low-dose radiation, 7 equivalent to the upper limit dose from a full-body spiral CT scan 8 and 2-4 Gy as high-dose radiation that causes substantial DNA damage to cells, 9,23 4 Gy is close to the LD50 for human whole-body exposure. 24 Using gH2AX as a surrogate marker of DNA damage, 23 we examined whether 0.1 Gy pretreatment of human fibroblasts could modulate cell sensitivity to a subsequent 4 Gy irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…11 Of note is the observation that low-dose IR-induced resistance seems not limited to irradiation, implicating an induction of a general cellular stress tolerance. 6 Under physiological conditions, the majority of differentiated cells use primarily mitochondrial oxidative phosphorylation to fully catabolize glucose for energy production. 20 Using a combined genetic, biochemical and metabolomics approaches, we demonstrate that low-dose radiation induces a metabolic switch from oxidative phosphorylation to aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the dose-effect curve would deviate from linearity with the dose and dose rate decreasing down to the background levels; the relationship can even become inverse in accordance with hormesis. A corresponding graph plotted on the basis of experimental data is presented in [73] with a comment that the window for maximum adaptive response protection occurs at doses between 1 and 100 mGy, where risk is reduced below the spontaneous level of cancer risk [73]. It means that a large part of experimental data is at variance with results of epidemiological studies discussed in [2,43].…”
Section: On the Dose-response Relationshipmentioning
confidence: 99%
“…The paper by Vaiserman (2010) reviews some of the abundant epidemiological and other data on radiation hormesis as it relates to cancer suppression. Mitchel (2010) points out in his paper that radiation adaptive responses occur in all organisms and describes a dose window (which corresponds to the hormetic zone) over which cancer suppression via stimulated adaptive protection occurs. The hormetic zone is thought to depend on the type of radiation (Scott 2005;Elmore et al 2009) and how the radiation is delivered (e.g., brief high rate vs. protracted low rate exposure [Elmore et al 2006;Feinendegen et al 2010]).…”
mentioning
confidence: 99%